Coeval primary and diagenetic carbonates in lacustrine sediments challenge palaeoclimate interpretations - Jeremy McCormack (Nature Portfolio, 2021)
Abstract Lakes are sensitive to climate change and their sediments play a pivotal role as environmental recorders. The oxygen and carbon isotope composition (δ18O and δ13C) of carbonates from alkaline lakes is featured in numerous studies attempting a quantitative reconstruction of rainfall, temperature and precipitation-evaporation changes. An often-overlooked challenge consists in the mineralogically mixed nature of carbonates themselves. We document a large variability of carbonate components and their respective distinct δ18O and δ13C values from sediments of Lake Van (Turkey) covering the last 150 kyr. The carbonate inventory consists of primary (1) inorganic calcite and aragonite precipitating in the surface-water, (2) biogenic calcite ostracod valves; and post-depositional phases: (3) dolomite forming in the sediment, and previously overlooked, (4) aragonite encrustations formed rapidly around decaying organic matter. We find a systematic relation between the lithology and the dominant deep-water carbonate phase formed recurrently under specific hydrological conditions. The presence of the different carbonates is never mutually exclusive, and the isotopic composition of each phase forms a distinctive cluster characteristic for the depth and timing of their formation. Our findings stretch the envelope of mechanisms forming lacustrine carbonates and highlight the urge to identify and separate carbonate components prior to geochemical analyses.